In India’s Sea of Darkness: An Unsustainable Island of Decentralized Energy Production - Singh, Kartikeya (Consilience, 2008)
Approximately 500 million people in India’s countryside are still without access to electricity. The government has launched an ambitious project to electrify the entire nation by 2012. Unfortunately, the term “village electrification” defines electricity distribution for only 10% of households. An equally ambitious plan by the Ministry of New and Renewable Energy states a goal to electrify about 25,000 of the remotest villages in India. In these villages, it is inefficient to extend the grid with decentralized, renewable energy systems. The economic development of a large portion of India’s population depends on the success of decentralized energy distribution. This development will help provide the means to eradicate poverty. Ensuring the success of these systems requires a closer look at the rural energy ladder. One must go beyond just lighting in order to establish a paradigm for integrated sustainable energy independence for India’s rural villages. Whether India decides to power its villages through grid-fed coal power or through decentralized renewable energy systems, this decision has major implications for global climate change. This study assesses the benefits and drawbacks of one such distributive power system: solar home lighting.